Bladder Neck Contractures Stabilize After Placement of the Artificial Urinary Sphincter. Issue 5 (30th May 2023) - Krughoff, Kevin; Peterson, Andrew C.
Abstract : Purpose: For male cancer survivors, the combination of stress urinary incontinence and recurrent bladder neck contracture presents a management dilemma with poor consensus. Our objective was to assess the impact of artificial urinary sphincter placement on bladder neck contracture recurrence among prostate cancer survivors with stress urinary incontinence and bladder neck contracture. Materials and Methods: Men electing artificial urinary sphincter placement at our institution undergo synchronous bladder neck contracture treatment if indicated. An institutional database was queried for men with stress urinary incontinence and ≥1 intervention for bladder neck contracture. Records were divided according to whether an artificial urinary sphincter was ever placed. The impact of artificial urinary sphincter placement on bladder neck contracture recurrence was assessed using a multivariable conditional survival analysis, with survival defined as the recurrence-free interval following bladder neck contracture intervention. The proportional hazards assumption was assessed on the basis of Schoenfeld residuals. Results: The analytic cohort consisted of 118 in the artificial urinary sphincter group and 88 in the non-artificial urinary sphincter group. Patients in both groups underwent a median of 2 (range 1-8) bladder neck contracture interventions over the entire course of their care, encompassing 445 total bladder neck contracture interventions. The artificial urinary sphincter group was on average 2.6 years younger ( P = .02) and had a higher pack-year smoking history ( P < .01). The presence of an artificial urinary sphincter was associated with a 61% lower bladder neck contracture re-intervention rate (HR 0.39, P < .01, CI 0.30-0.50) at any time when accounting for number of prior bladder neck contracture interventions and bladder neck contracture risk factors. Conclusions: Artificial urinary sphincter placement is associated with a lower rate of bladder neck contracture re-intervention. Artificial urinary sphincter placement should not be delayed or avoided due to the presence of bladder neck contracture.